PENGARUH EDUKASI SIMULATION GAME MELALUI “MOTOMALAM” TERHADAP PENGETAHUAN SISWA MI DARUL HIKAM TENTANG PERTOLONGAN PERTAMA TENGGELAM DI DS. TRACAL KEC. KARANGGENENG KAB. LAMONGAN: PENGARUH EDUKASI SIMULATION GAME MELALUI “MOTOMALAM” TERHADAP PENGETAHUAN SISWA MI DARUL HIKAM TENTANG PERTOLONGAN PERTAMA TENGGELAM DI DS. TRACAL KEC. KARANGGENENG KAB. LAMONGAN - Triviana, Rima Arinda; Hidayati, Nur; Kusbiantoro, Dadang; Jaenudin, Muhammad Fadoli (Jurnal Surya, 2025)
Introduction: Drowning incidents in children are frequently found, because children are a group that is vulnerable to drowning and cannot swim. Children's knowledge of first aid for drowning is still low. The aim of the study was to analyze the effect of education on first aid for drowning through the simulation game on students' knowledge. Methods: The research design used a pre-experimental one-group pre-post test on 56 students of elementary school grades 4-6 taken by total sampling. The intervention provided is in the form of simulation games education through. This research was conducted on July 26-28, 2023 at an elementary school, research data was collected through a knowledge questionnaire. Results: The results of the study showed that the level of knowledge before being given simulation games education about first aid for drowning was found that most (71.4%) of 40 students had insufficient knowledge. After being given an educational simulation game about first aid for drowning, almost all (82.1%) had an increased level of knowledge in 46 students. The results of the Wilcoxon test showed that there was an effect of educational simulation games on the knowledge of elementary school students about Drowning First Aid with a significant (p=0.000). Conclusion: The use of simulation games Drowning First Aid Monopoly can be used as an educational medium and has the potential to increase knowledge about first aid for drowning in children. Keywords: Drowning, Knowledge, Simulation Game